Selective inhibition of cancer cell self-renewal through a Quisinostat-histone H1.0 axis - Cristina Morales Torres; Mary Y. Wu; Sebastijan Hobor; Elanor N. Wainwright; Matthew J. Martin; Harshil Patel; William Grey; Eva Grönroos; Steven Howell; Joana Carvalho; Ambrosius P. Snijders; Michael Bustin; et al. (Nature Communications, 2020)
Targeting self-renewing cancer cells without deleterious side effects in normal tissues has proven challenging. Here, the authors show that the well-tolerated HDAC inhibitor Quisinostat safely inhibits tumor maintenance and disease relapse by restoring high levels of histone H1.0.